Strain effect on the optical nonlinearity in an InGaAs/GaAs asymmetric Fabry-Perot modulator. - HEGARTY, JOHN (American Physical Society, 1993)
The effect of strain on the optical nonlinearities and operation of an all-optical asymmetric Fabry-Perot italon is investigated. A high reflectivity modulation of 60% is reported with a contrast ratio of 12.2:1 and insertion loss of 1.87 dB. High contrast is achieved through absorption matching requiring a thick active layer. The effect of a thick structure on the strain reduced saturation carrier density is measured. The saturation density is calculated to be a factor of 2.5 less than in a similar GaAs modulator, showing thicker strained devices still display the advantages of thinner structures.
PUBLISHED
Keywords: Physics